2009
DOI: 10.3174/ajnr.a1483
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging Findings in Autosomal Recessive Hereditary Spastic Paraplegia

Abstract: BACKGROUND AND PURPOSE:Hereditary spastic paraplegia (HSP) is a disorder characterized by degeneration of the corticospinal tracts and posterior column of the spinal cord. Previously described radiologic findings included nonspecific brain abnormalities such as brain atrophy and white matter lesions, as well as atrophy of the spinal cord. In our study, we aimed to better characterize brain and spine MR imaging findings in a series of patients with HSP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 33 publications
2
30
0
4
Order By: Relevance
“…Several recent studies using conventional MRI scans revealed an atrophic or dysplastic corpus callosum in different HSP subtypes such as SPG11 ‐asssociated complicated ARHSP or SPG4 ‐associated pure autosomal dominant HSP 39–42. In this context, our findings of a subtle reduction of white matter integrity in the corpus callosum of heterozygote SPG7 ‐ARHSP carriers may suggest that different HSP‐related genes share a common biological pathway leading to neurodegeneration of the corpus callosum 43…”
Section: Discussionsupporting
confidence: 54%
“…Several recent studies using conventional MRI scans revealed an atrophic or dysplastic corpus callosum in different HSP subtypes such as SPG11 ‐asssociated complicated ARHSP or SPG4 ‐associated pure autosomal dominant HSP 39–42. In this context, our findings of a subtle reduction of white matter integrity in the corpus callosum of heterozygote SPG7 ‐ARHSP carriers may suggest that different HSP‐related genes share a common biological pathway leading to neurodegeneration of the corpus callosum 43…”
Section: Discussionsupporting
confidence: 54%
“…White matter changes are present in FAHN and are also a core element of leukodystrophies. Presence of a thin corpus callosum seen in FAHN is also a hallmark feature in some of the HSPs [113]. …”
Section: Fa2h-associated Neurodegeneration (Fahn)/ Spg35mentioning
confidence: 99%
“…[2][3][4] Autosomal recessive forms of HSP comprise mainly 'complicated' clinical types with extensive neurological and non-neurological manifestations. [5][6][7] The majority of HSP genes are associated with very rare or even unique clinical forms.…”
Section: Introductionmentioning
confidence: 99%